Kombucha microbiome as a probiotic: a view from the perspective of post-genomics and synthetic ecology - Kozyrovska, N.O.; Reva, O.M.; Goginyan, V.B.; de Vera, J.-P. (Вiopolymers and Cell, 2012)
Probiotics are essential for establishing and maintaining optimal immune health. The probiotic therapy is known from alternative medicine for ages; however, the recent demonstration of the normal microflora to induce innate immunity has introduced the science-based concept of therapeutic application of potentially beneficial probiotic microorganisms for a treatment of functional disorders. Traditionally, probiotics are associated with dairy products, however, novel formulations are needed, first of all, originated from naturally occurring symbiotic microbial communities as the most robust assemblages. Especially, safe and robust probiotics are needed for long-term expeditions, outposts, extraterrestrial permanently-manned bases, where humans are exposed to adverse environmental factors. Kombucha beverage is Symbiotic Culture of Bacteria and Yeast (SCOBY) and associated with health-promoting effects. Kombucha tea/mat is being in use in human livings within millennia as a probiotic drink for healing and health prophylaxis effects, however, new research opportunities promise its «renaissance», going to be used pharmacologically. Keywords: probiotics, kombucha microbiome, post-genomics, synthetic ecology